VERMICULITE WITH AG AND CU USED AS AN ANTIBACTERIAL NANOFILLER IN POLYETHYLENE - Hundáková, Marianna; Valášková, Marta; Samlíková, Magda; Pazdziora, Erich (GeoScience Engineering, 2014)
Vermiculite (Ver) enriched with silver and copper was used as nanofiller to the polyethylene (PE) matrix. Specifically, the low density polyethylene (LDPE) was chosen as a matrix. The samples Ver-Ag,Cu were prepared by shaking of Ver with the aqueous solutions of silver and copper nitrate. The mixtures of the Ver nanofillers and PE were homogenized by melt compounding technique and further thin plates were pressed from stiff matter of PE with Ver nanofiller. The exfoliation of the powdery Ver nanofillers in PE matrix was characterized by the X-ray diffraction analysis of thin plates. Distribution of Ver nanofiller in PE matrix was observed by Light microscopy. The reinforcing effect of nanofillers onto PE matrix was studied by creep experiment. Antibacterial activity of powder Ver-Ag,Cu samples and surfaces of PE/Ver-Ag,Cu samples was tested on the Gram-positive bacteria Enterococcus faecalis. All tested PE/Ver-Ag,Cu surfaces showed good antibacterial behaviour after 24 h in comparison to pure PE. The number of colonies decreased from the countless number to several hundred colonies.